A structure–activity relationship of non-peptide macrocyclic histone deacetylase inhibitors and their anti-proliferative and anti-inflammatory activities. Issue 24 (15th December 2015) - Tapadar, Subhasish; Fathi, Shaghayegh; Raji, Idris; Omesiete, Wilson; Kornacki, James R.; Mwakwari, Sandra C.; Miyata, Masanori; Mitsutake, Kazunori; Li, Jian-Dong; Mrksich, Milan; Oyelere, Adegboyega K.
Graphical abstract: Abstract: Inhibition of the enzymatic activity of histone deacetylase (HDAC) is a promising therapeutic strategy for cancer treatment and several distinct small molecule histone deacetylase inhibitors (HDACi) have been reported. We have previously identified a new class of non-peptide macrocyclic HDACi derived from 14- and 15-membered macrolide skeletons. In these HDACi, the macrocyclic ring is linked to the zinc chelating hydroxamate moiety through a para -substituted aryl-triazole cap group. To further delineate the depth of the SAR of this class of HDACi, we have synthesized series of analogous compounds and investigated the influence of various substitution patterns on their HDAC inhibitory, anti-proliferative and anti-inflammatory activities. We identified compounds25b and38f with robust anti-proliferative activities and compound26f (IC50 47.2 nM) with superior anti-inflammatory (IC50 88 nM) activity relative to SAHA.